2023
DOI: 10.3389/fmolb.2023.1089213
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of heterologous ubiquitination including linear ubiquitination in Alzheimer’s disease and amyotrophic lateral sclerosis

Abstract: In neurodegenerative diseases such as Alzheimer’s disease (AD) and amyotrophic lateral sclerosis (ALS), the progressive accumulation of ubiquitin-positive cytoplasmic inclusions leads to proteinopathy and neurodegeneration. Along with the seven types of Lys-linked ubiquitin chains, the linear ubiquitin chain assembly complex (LUBAC)-mediated Met1-linked linear ubiquitin chain, which activates the canonical NF-κB pathway, is also involved in cytoplasmic inclusions of tau in AD and TAR DNA-binding protein 43 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…Ubiquitination is a fundamental post-translational modification that controls the function and levels of target proteins. Recently, linear ubiquitin (UB) chains released from ubiquitinated proteins have emerged as an important form of ubiquitin assembly that may play regulatory roles for many cellular processes, such as immune responses and proteostasis (11,15,17,(20)(21)(22)(23)(24)44). Our previous studies in Drosophila melanogaster demonstrated the versatility of transgene-expressed linear poly-ubiquitin chains that cannot be dismantled into single ubiquitin moieties, which can be conjugated to target proteins or, alternatively, can be themselves ubiquitinated and degraded (20,28,29,45).…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination is a fundamental post-translational modification that controls the function and levels of target proteins. Recently, linear ubiquitin (UB) chains released from ubiquitinated proteins have emerged as an important form of ubiquitin assembly that may play regulatory roles for many cellular processes, such as immune responses and proteostasis (11,15,17,(20)(21)(22)(23)(24)44). Our previous studies in Drosophila melanogaster demonstrated the versatility of transgene-expressed linear poly-ubiquitin chains that cannot be dismantled into single ubiquitin moieties, which can be conjugated to target proteins or, alternatively, can be themselves ubiquitinated and degraded (20,28,29,45).…”
Section: Discussionmentioning
confidence: 99%
“…However, G186R-type SHARPIN appeared to be uniformly distributed in the cytoplasm by immunocytochemistry, whereas it exhibited instability in the soluble fraction of the cell lysate, likely forming aggregates, making extremely difficult of quantitative analysis. Recently, Sato et al [ 36 ] clarified the impact of the G186R mutation from the perspective of structural biology in their review, and they predicted reduced interaction between SHARPIN and HOIL1. They also speculated that glycine at this position in the crystal structure of mouse LUBAC is located in the turn region that connects two helices and that the structure is destabilized by dihedral angle restrictions with residues other than glycine.…”
Section: Discussionmentioning
confidence: 99%
“…78, 79 During ubiquitin-dependent proteolysis, the C-terminal Gly76 of ubiquitin is reversibly ligated to target proteins or other ubiquitin molecules. 78 Typically, ubiquitin forms polyubiquitin chains through seven internal lysine (K) residues: K6, K11, K27, K29, K33, K48, and K63. Among these, K48-linked ubiquitination is the most common and primarily triggers proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, there are only two ubiquitin-activating enzymes (E1s), ∼40 ubiquitin-conjugating enzymes (E2s), and over 600 ubiquitin-ligase enzymes (E3s) that regulate ubiquitination. 78, 79 During ubiquitin-dependent proteolysis, the C-terminal Gly76 of ubiquitin is reversibly ligated to target proteins or other ubiquitin molecules. 78 Typically, ubiquitin forms polyubiquitin chains through seven internal lysine (K) residues: K6, K11, K27, K29, K33, K48, and K63.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation